2019
DOI: 10.1073/pnas.1819481116
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of Phytophthora suppressor of RNA silencing 2 (PSR2) reveals a conserved modular fold contributing to virulence

Abstract: Phytophthora are eukaryotic pathogens that cause enormous losses in agriculture and forestry. Each Phytophthora species encodes hundreds of effector proteins that collectively have essential roles in manipulating host cellular processes and facilitating disease development. Here we report the crystal structure of the effector Phytophthora suppressor of RNA silencing 2 (PSR2). PSR2 produced by the soybean pathogen Phytophthora sojae (PsPSR2) consists of seven tandem repeat units, including one W-Y motif and six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…Both tyrosine and phenylalanine are aromatic amino acids; however, the hydroxyl group on tyrosine makes it slightly bulkier, more polar, and introduces a potential phosphorylation site. Variation in this region is not uncommon in other oomycete species: the fifth of the seven domains in Psr2 of P. sojae has an F instead of a Y and is similar in structure to the single domain of ATR1 in H. arabidopsidis that has a cysteine at the Y position [31]. Further structural characterization is needed to reveal whether these substitutions alter tertiary structure and biological function.…”
Section: Plos Pathogensmentioning
confidence: 99%
See 2 more Smart Citations
“…Both tyrosine and phenylalanine are aromatic amino acids; however, the hydroxyl group on tyrosine makes it slightly bulkier, more polar, and introduces a potential phosphorylation site. Variation in this region is not uncommon in other oomycete species: the fifth of the seven domains in Psr2 of P. sojae has an F instead of a Y and is similar in structure to the single domain of ATR1 in H. arabidopsidis that has a cysteine at the Y position [31]. Further structural characterization is needed to reveal whether these substitutions alter tertiary structure and biological function.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Structural analysis on four different RXLR effectors from Phytophthora infestans (Avr3a and PexRD2), P. capsici (Avr3a11), and the downy mildew pathogen H. arabidopsidis (ATR1) revealed that the W and Y motifs form a~50 amino acid alpha-helical fold that may play a role in protein-protein interactions [27][28][29][30]. This effector-associated fold, termed the WY domain after its conserved tryptophan and tyrosine residues, is highly structurally conserved between effectors from multiple Peronosporales species, despite sharing less than 20% sequence similarity across the whole domain [27,31]. The WY domain appears to be specific to the Peronosporales and was predicted to be present in nearly half of the RXLR effectors of P. infestans and a quarter of the RXLR effectors in H. arabidopsidis [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The P. infestans genome harbors over 500 predicted RXLR effectors that are grouped into ~150 families and tend to exhibit sequence and expression polymorphisms between pathogen strains (Haas et al, 2009;Cooke et al, 2012;Yoshida et al, 2013;Pais et al, 2018). RXLR effectors are modular proteins with the N-terminal signal peptide and RXLR region mediating secretion and translocation into host cells, and the C-terminal end, often defined by the WY/LWY fold, carrying the effector biochemical activity (Whisson et al, 2007;Win et al, 2012a;He et al, 2019). To date, over a dozen P. infestans RXLR effectors have been functionally characterized for their virulence activities (Rovenich et al, 2014;Anderson et al, 2015;Du et al, 2015;Wang et al, 2015;Boevink et al, 2016;Dagdas et al, 2016;Yang et al, 2016;Turnbull et al, 2017;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The structure may llow the evolution of effectors to maintain their function while evading recognition by the plant immune system [77]. Effectors with WY-folds were thus far implicated in various processes such as RNA silencing suppression (Phytophthora suppressor of RNA silencing 2 (PSR2, P. sojae) and manipulation of vesicular trafficking (PexRD54, P. infestans) [78,79].…”
mentioning
confidence: 99%